PEMIKIRAN MAZHAB IQTISHADUNA DAN NEO-REVIVALIS - Iva Ashari Ananda; Evin Juliasti; Sumar’in Sumar’in (Adisam Publisher, 2025)
The Iqtishaduna school was pioneered by Muhammad Baqr Sadr, according to him Islamic economics is a method or path that Muslims choose to follow in order to achieve their economic life and in solving practical economic problems, in line with his concept of justice. Muhammad For Sadr, Islam does not deal with the law of supply and demand, nor the relationship between profit and interest, the phenomenon of diminishing returns which is the science of economics. In this research the author used a qualitative method with the type of Library Research research. Some of the main economic thoughts contained in the Iqtishâduna book include the definition of Islamic economics, the characteristics of Islamic economics, the theory of production and distribution, of which almost one third receives a discussion portion. Apart from that, it is impossible to implement Islamic economic ideas without the government's role in the economic sector. The role of government in Muhammad Baqir Sadr's conception is related to efforts to realize prosperity in the midst of human life. Two important roles of the government in this case are realizing social security and social balance. Meanwhile, Islamic neo-revivalism is a movement that wants to restore world order with an Islamic caliphate which is believed to be the order taught in Islamic teachings.